HPLC Estimation of Gliclazide in Formulations and In Pharmacokinetic Studies - Chowdary, K.P.R.; Tripura Sundari, P. (Asian Journal of Chemistry, 2010)
A simple, accurate and sensitive RP-HPLC method was developed and validated for the estimation of gliclazide in bulk drug samples, its formulations and in plasma samples using RP C-18 column with UV detection at 230 nm. The mobile phase consists of water containing 0.1 % w/v sodium phosphate monobasic (pH adjusted to 2.1 using phosphoric acid) and acetonitrile (34:66). The retention time for gliclazide was 5.4 min. The intra- and inter-day coefficient of variation was less than 1.28 % showing high precision of the method. The method was highly accurate with a recovery in the range 99-100 %. The method was found suitable for estimating gliclazide in plasma samples in pharmacokinetic studies. The pharmacokinetic parameters of gliclazide estimated employing the HPLC method developed agreed well with the literature values.